The Effect of Household Consumption, Investment, and Capital Expenditure on Gross Regional Domestic Product in the Special Region of Yogyakarta Province - Mutiara Latifah; M Taufiq (Journal of Economics and Management Scienties, 2026)
The Special Region of Yogyakarta possesses unique characteristics while its per capita income is relatively low compared to other provinces on Java, its happiness index is notably high, necessitating further study into the factors influencing its economic growth. This study aims to analyze the influence of household consumption, investment, and capital expenditure on GRDP in the Special Region of Yogyakarta Province. The method used is panel data regression by combining time series for the period 2015–2024 and cross-regional data from 5 districts/cities in the Special Region of Yogyakarta Province. The analysis assesses the partial and simultaneous influence of independent variables on the dependent variable. The findings show that household consumption and capital expenditure have a positive influence on GRDP, while investment does not show a significant effect. However, simultaneously, all three variables contribute to GRDP in the Special Region of Yogyakarta Province. Based on these findings, it is recommended that regional policies be focused on increasing people's purchasing power, improving the quality of investment that can create linkages with the local sector, and allocating more strategic capital expenditures on infrastructure development and public facilities to encourage sustainable economic growth in the Special Region of Yogyakarta Province.